Single Phase Matrix Converter operating as a Four Quadrant DC chopper controlled using Xilinx FPGA / Siti Zaliha Mohammad Noor, Abdul Rahman N.F. and Hamzah M.K. - Mohammad Noor, Siti Zaliha; Abdul Rahman, N.F; Hamzah, M.K (UiTM Press, 2011)
This paper is concerned on FPGA design for control implementations of the Single-Phase Matrix Converter (SPMC) operating as a Four Quadrant DC Chopper. The Pulse Width Modulation (PWM) technique is used to synthesize the output voltage with. The power circuit uses the Insulated Gate Bipolar Transistor (IGBT) as switching device in the SPMC implementation. Safe-commutation strategy was incorporated to solve switching transients. The Power System Block Set (PSB) within the MATLAB/Simulink (MLS) environment is used to study the behaviour of the proposed converter. A Xilinx Field Programmable Gate Array (FPGA) was used at the heart of the control electronics, implemented to verify operation. Selected simulation and experimental results are presented. It has been shown that the FPGA could effectively be used in SPMC with the four bidirectional switching arrangements. Experimental results achieve good agreement with those predicted in simulations.